The Effect of Competency Needs and Training Facilities on the Participation Rate of Competency-Based Training Participants at LLK Selong East Lombok Regency - rahmi, Rahmi; Laskarwati, Batari (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
One of the serious challenges facing Indonesia is unemployment. Statistical data published by BPS in 2020 recorded the number of unemployed people in Indonesia at 9.77 million people. The Global Competitiveness Index explains that Indonesia is far behind compared to neighboring countries Indonesia is still in 50th position with a score of 64.5 while Malaysia is in 27th position with a score of 74.6. Singapore alone is in first place in the world with a score of 84.8. One of the efforts to overcome this problem is to provide PBK activities to the community, so that they can be absorbed in the world of work and industry. This study aims to analyze how competency needs and the availability of training facilities affect the level of participant participation. The research method used is a survey approach with a questionnaire as a data collection instrument. The sample of this study was 106 respondents out of 144 participants. Data analysis was conducted using multiple linear regression. Data analysis was conducted with multiple linear regression. The results showed that competency needs have a significant effect on the level of participant participation (p-value: 0.002 <?.0.05). Likewise, the existence of training facilities has a significant effect on the level of participation of PBK participants at LLK Selong (p-value: 0.049 <?.0.05). Based on the conclusions of this study, it is recommended to pay attention to the competency needs of participants and provide adequate training facilities to increase participation in PBK activities at LLK Selong, East Lombok Regency